2019
DOI: 10.1002/ejlt.201900129
|View full text |Cite
|
Sign up to set email alerts
|

Preservative Effect of Algae Extracts on Lipid Composition and Rancidity Development in Brine‐Canned Atlantic Chub Mackerel (Scomber colias)

Abstract: This research focuses on the lipid fraction and the rancidity stability of commercial canned Atlantic Chub mackerel (Scomber colias). For it, two different concentrations of aqueous extracts of two abundant algae (Fucus spiralis and Ulva lactuca) are included in the brine‐packing (aq. 2% NaCl) medium during mackerel canning. Quality analyses are carried out after a 3‐month canned storage (20 °C). Phospholipids, sterols, and α‐tocopherol contents show a marked loss as a result of canning, this loss being mostly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
33
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 24 publications
(60 citation statements)
references
References 45 publications
(75 reference statements)
7
33
1
Order By: Relevance
“…In agreement with the current study, previous research has shown an increasing effect on peroxides content in canned fish by increasing the B. bifurcata water-extract [39] or the U. lactuca and F. spiralis brine-extract [19] contents in the packaging media employed for mackerel canning. In both studies, it was considered that peroxides breakdown was partially avoided as a result of the algae extract presence.…”
Section: Determination Of Lipid Oxidation Developmentsupporting
confidence: 93%
See 3 more Smart Citations
“…In agreement with the current study, previous research has shown an increasing effect on peroxides content in canned fish by increasing the B. bifurcata water-extract [39] or the U. lactuca and F. spiralis brine-extract [19] contents in the packaging media employed for mackerel canning. In both studies, it was considered that peroxides breakdown was partially avoided as a result of the algae extract presence.…”
Section: Determination Of Lipid Oxidation Developmentsupporting
confidence: 93%
“…According to the present study, no effect of the alga extract concentration was produced on the FFA content of canned Atlantic mackerel (Scomber scombrus) packaged with an aqueous extract of macroalga Bifurcaria bifurcata [39]. Contrary, an increased formation of FFA was implied in canned Atlantic chub mackerel (S. colias) by increasing the presence of macroalgae Ulva lactuca and F. spiralis extracts in the packaging system [19].…”
Section: Determination Of Lipid Hydrolysis Developmentcontrasting
confidence: 50%
See 2 more Smart Citations
“…Other work also stated the preservative ability of polyphenols obtained from Fucus spiralis and U. lactuca when incorporated as a canning medium for Scomber colias . The presence of the algae inhibited the breakdown of free fatty acids and the increment in the peroxide value, especially for samples treated with F. spiralis [ 167 ]. Therefore, the incorporation of algae compounds into fish or shellfish matrixes provides extended storage periods while reducing the microorganism growth rate, which ultimately improves food safety.…”
Section: Incorporation To the Food Industrymentioning
confidence: 99%